Quantitative analysis of biological membrane lipids at the low picomole level by nano-electrospray ionization tandem mass spectrometry - Brügger, B. (The National Academy of Sciences of the USA, 1997)
Nano-electrospray tandem mass spectrometry allows qualitative and quantitative analysis of complex membrane lipid mixtures at the subpicomole level. We have exploited this technique to selectively detect individual classes of phospholipids from unprocessed total cellular lipid extracts by either precursor ion or neutral loss scanning. This way phosphatidylcholine, sphingomyelin, phosphatidylinositol and -phosphates, phosphatidylethanolamine, phosphatidylserine, phosphatidylglycerol, phosphatidic acid, and their plasmalogen analogues can be detected. The optimized ionization and fragmentation conditions described together with the principle of internal standardization by nonnatural analogues allow the rapid and quantitative determination of membrane lipid compositions down to sample amounts of 1000 cells.